Pengaruh Green Product Dan Green Promotion Terhadap Green Purchase Behavior Pada Konsumen Fore Coffee Cabang Sun Plaza Medan - Angeline Br Marbun, Yuana Widya; Manihuruk, William Dika; Wahyu, Alvin Pratama; Nabilah Rangkuti, Rizqa; Eliza Juriono, Sophia Nur (PT. Alahyan Publisher Sukabumi, 2024)
This study aims to examine the influence of Green Product and Green Promotion on consumers Green Purchase Behavior at Fore Coffee, Sun Plaza Medan branch. The background of this research is based on the rapid growth of the coffee industry in Indonesia and the increasing consumer awareness of environmental issues. The research method employed is a survey with a population consisting of consumers who have purchased Fore Coffee products. A sample of 100 respondents was selected using incidental sampling techniques. Data were collected through questionnaires and analyzed using multiple linear regression. The results show that the Green Product variable does not have a significant influence on Green Purchase Behavior, while Green Promotion has a significant effect. Simultaneously, both variables have a significant influence on Green Purchase Behavior. These findings provide insights into the importance of green marketing strategies in promoting environmentally friendly purchasing behavior among consumers.